ANALYSIS OF THE IMPLEMENTATION OF STANDARD OPERATING PROCEDURES TO IMPROVE OUTPATIENT REGISTRATION SERVICES AT LABUHAN DELI COMMUNITY HEALTH CENTER - Tiara Pakar Ningrum; Dewi Agustina (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOPs) in improving outpatient registration services at a primary health center in Indonesia. A qualitative case study design was employed, with data collected through in-depth interviews, direct observations, and document review involving ten informants, including health center management, registration and medical record officers, and outpatient service users. Data were analyzed using an interactive analysis model to identify factors supporting and hindering SOP implementation. The findings indicate that outpatient registration SOPs have been implemented systematically, with successful implementation influenced by staff competence, understanding of procedures, and active patient participation. Several challenges, such as limited patient compliance and technical disruptions, were identified; however, these barriers were effectively addressed through direct patient education, regular SOP socialization, continuous monitoring and evaluation, and open communication among staff. These efforts contributed to improved service flow and enhanced service quality in outpatient registration. Strengthening SOP dissemination, improving staff capacity, and reinforcing patient education are recommended as policy strategies to ensure sustainable improvements in outpatient registration services at primary healthcare facilities.